The REM-sleep-related characteristics of narcolepsy: a nation-wide multicenter study in Turkey, the REMCON study - (:unkn) unknown (My University, 2022)
ntroduction: Narcolepsy type 1 (NT1) is caused by hypocretin deficiency, the pathophysiology of narcolepsy type 2 (NT2) has not been delineated. Except for the hypocretin deficiency and cataplexy, all clinical and laboratory features used in the diagnosis of NT2 are identical to those used for NT1. The aim of this study was to assess the rapid eye movement (REM) sleep-related characteristics in the patients with narcolepsy; the characteristics of REM sleep in polysomnography (PSG) and multiple sleep latency test (MSLT) recordings, the quantification of REM sleep without atonia (RSWA) and atonia index, and the analysis of rapid eye movements (REMs) during REM sleep. Materials and methods: This study was planned by the Sleep Medicine Study Group of the Turkish Neurology Society, and conducted in 11 centers in eight cities in Turkey. The analysis of RSWA was analyzed by reviewing all REM sleep periods on nocturnal PSG and MSLT recordings per standard criteria. The total duration of the increased muscle tone during REM sleep in the chin and bilateral leg electromyography (EMG) recordings was calculated as RSWA index. The REMs index was also investigated the relation to the RSWA. Results: A total of 274 patients were involved; 147 patients (53.6%) were males and 127 patients (46.4%) were females; the mean age was 29.1 ± 12.0 years. The diagnosis of NT1 was made in 166 patients (60.6%), and 108 patients (39.4%) were diagnosed as having NT2. The mean Epworth sleepiness scale score was significantly higher in patients with NT1 than the patients with NT2 (P ¼ 0.001). The diagnosis of REM sleep behavior disorder (RBD) was made in 19.3% of the patients with NT1 versus in 2.8% of the patients with NT2 (P < 0.001). The percentage of SOREMP in PSG recordings was significantly higher in patients with NT1 (37.1%) than those with NT2 (18.9%, P ¼ 0.001). MSLT showed that the mean sleep latency was shorter in patients with NT1 compared to those with NT2 (P < 0.001). The total duration of REMs on electrooculography recordings was also significantly higher in patients with RSWA in comparison with the patients without RSWA (P ¼ 0.002). Total duration of REMs was significantly and positively correlated with the duration of RSWA on chin-EMG and leg-EMG recordings (P ¼ 0.001). ROC analyses showed an RSWA index of 2% for the RSWA on chin-EMG with a sensitivity of 86.7% and a specificity of 71.3% (P < 0.001). The REMs index 20% was associated with the presence of RSWA with a sensitivity of 70.0% and a specificity of 57.1% (P ¼ 0.008). Conclusions: In this nation-wide study, we identified for the first time that the increase in REMs density during REM sleep may be a major correlate of the RSWA. Significant positive correlations were demonstrated between the total duration of REMs on electrooculography recordings and the mean durations of RSWA in both chin and leg EMG recordings. A REMs index of >20% was demonstrated to have a moderate sensitivity and specificity in the diagnosis of RSWA. As observed in chin RSWA index, REMs index also showed a significantly high association with RBD, in comparison to RSWA per standard criteria.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Nöroloji; Medicine; Health Sciences; Internal Medicine Sciences; Neurology; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Nöroloji (klinik); Yaşam Bilimleri; Neurology (clinical); Life Sciences; Narcolepsy; REM sleep; REM sleep Without atonia; Rapid eye movement index; PERIODIC LEG MOVEMENTS; LATENCY TEST; EYE-MOVEMENTS; CATAPLEXY; MSLT; HYPERSOMNIA; TYPE-1; WAKEFULNESS; PREDICTORS; DIAGNOSIS; Narcolepsy; REM sleep; REM sleep Without atonia; Rapid eye movement index